Genetic variation in Moringa stenopetala germplasm of Ethiopia by using RAPD as genetic marker - Beyene, D. (Addis Ababa University, 2005)
The germplasm of Moringa stenopetala were assessed for genetic divergence within and among populations. Nineteen accessions that were represented by seventy-one individuals were studied. A total of 251 unambiguous bands were scored from OPA-13 primers. No common band was found for the entire populations. The range of mean diversity estimates of Shannon's index varies from 0.00 for Lasho and Berber to 0.3623 for Konso Gamolle within populations and the entire population was found to have the index of 0.3124. Similarly, Nie's mean estimates of diversity within populations range from 0.00 for Lasho and Berber to 0.2440 for Konso Gamolle and its entire population mean was 0.1818. The phenetic tree (dedrogram) constructed to evaluate relationships within populations was unable to discriminate 42% of the analyzed accessions. On the other hand, the range of the genetic distance was 0.00 to 0.41 and with a mean of 0.09.The genetic variability among the accessions was found to be low